Stress Management Strategies as Correlates of Librarians’ Task Performance - Isaac, Usuka Enweremadu; Umaru, Isaac Abu; Rosemary, Odiachi Anwuli; Chimaobi, Ekere Felix (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 2 (2020): Journal of Advanced Research in Humanities and Social Science, 2020)
The task performance of librarians is their ability to carry out their assigned library house-keeping duties and tasks very well. The study investigated stress management strategies as correlates of librarians’ task performance. The study was guided by 2 specific objectives and research questions. The study tested 2 null hypotheses on a 0.05 level of significance. A correlational survey research design was adopted for the study. The population of the study was 191 librarians. The sample size was 191 librarians; the entire population was studied, therefore, no sampling was done. Data were collected with a pair of questionnaires. Standard linear regression analysis was used to test the null hypotheses on a 0.05 level of significance; whereas, Pearson Product Moment Correlational Coefficient (PPMCC) was used to analyze data for the research questions. The findings of the study show that there is a significant (0.00 > 0.05) and a high (r = 0.71, R 2 = 0.50) relationship between individual stress management strategies and librarians’ task performance; and there is a significant (0.00 > 0.05) and high (r = 0.61, R 2 = 0.38) relationship between organizational stress management strategies and librarians’ task performance. In line with these findings, the study recommends that Librarians should frequently consult stress management experts such as psychologists and physiotherapists to guide and sensitize them on the appropriate stress management practices they should engage in daily; and the library managers should ensure that they employ organizational stress management strategies in carrying out their administrative functions. How to cite this article: Isaac UE, Umaru IA, Rosemary OA. Stress Management Strategies as Correlates of Librarians’ Task Performance. J Adv Res Humani Social Sci 2020; 7(2): 32-40.